Upaya Keluarga Mengolah Makanan Bergizi dengan Bahan Pangan Lokal dalam Mencegah Stunting - Ravika Virnanda; Solfema Solfema; Lili Dasa Putri (Universitas Maritim AMNI Semarang, 2024)
This article examines family efforts to prevent stunting through nutritious food processing based on local food ingredients. Stunting, as a result of chronic malnutrition in the first thousand days of life, threatens the quality of physical growth, cognitive development, and long-term productivity. The utilization of local food ingredients such as vegetables, fruits, animal protein, and regional carbohydrates is considered a strategic solution that is affordable, nutritious, and easily accessible. Through a literature review method, this article explores the economic and health benefits of local foods and the importance of creativity in their processing. The study emphasizes the role of families in creating a balanced diet, encouraging healthy eating habits and supporting a stunting-free generation. The conclusion of this article highlights the importance of a multisectoral approach to sustainable stunting prevention, in order to create a healthier and more productive future for the nation.